The preposed object in Mandarin Chinese and Southern Mi - Kuo, Pei-Jung (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 2008)
In this paper I discuss a preposed object construction in two Chinese dialects, Mandarin and Southern Min. An example of a preposed object is shown in (3). As one can see when comparing with (1), the object now is located between the subject and the verb. Note that this object preposing is different from the typical topicalization in (2), where the object moves to the left of the subject. (1) Geruisen kan-wan-le [dp zheben shu]. (SVO) Grissom read-flnish-ASP this-CL book ‘Grissom finished reading this book’ (2) [dp zheben shu], Geruisen kan-wan-le (OSV / topicalization) this-CL book Grissom read-finish-ASP (3) Geruisen [d p zheben shu] kan-wan-le. (SOV) Grissom this-CL book read-finish-ASP The preposed object in Mandarin is believed to be optional, as shown in (4) (cf. Ernest and Wang (1995) and many others). However, as claimed by Lee (2007), the preposed object is obligatory in Southern Min in the environment in (5). The object cannot stay in postverbal position. (4) a. Abing zhi wan [dp fan] le Abing eat finish rice PERF ‘Abing has finished eating the rice.’ b. Abing [Dp fan] zhi wan le Aing rice eat finish PERF (5) a.* Abing chah oan [Dp png] a Abing eat finish rice PERF ‘Abing has finished eating the rice.’ b. Abing [dp png] chah oan a Aing rice eat finish PERF In the following discussion, I will first argue that the preposed object in both dialects is a topic, but not a focus as generally claimed in the literature. Furthermore, I will show that the above contrast in Mandarin and Southern Min is not due to different syntactic strategies of object preposing in these two dialects, but it is a result of tone combination differences in these two languages.